The Motif of Jacob’s Ladder (Gen 28:10–22) in the Ancient Symbolism of Western Christianity - Bardski, Krzysztof (Collectanea Theologica, 2021)
The “Jacob’s ladder” episode from the book of Genesis inspired numerous symbolic interpretations in ancient Christianity. Most often we encounter moral symbolism, which basically proceeds in two directions. Following Tertullian, “descending angels” symbolize sinners, and “ascending” – righteous people. According to Augustine, “descending” mean those who take care of the needs of others, while “ascending” are those who direct their hearts to God. For Jerome, ascending and descending angels symbolize not so much people as the mercy of God who descends to the sinner, whereas for Ambrose and Zeno of Verona the ladder represents the Old and New Testament, and its rungs – the Christian virtues. An important literary motif in the story of the “Jacob’s ladder” is the stone under the Patriarch’s head, which in the Christian tradition assumes a Christological meaning.